The Relevance Of Protectıng Debtor Customer Data And Informatıon Through Bank Secrecy: A Comparatıve Study In Indonesıa, Malaysıa And The Unıted Kıngdom - Putriyanti, Erma Defiana; Abdul Rachmad Budiono; Sukarmi, Sukarmi; Reka Dewantara (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to examine and analyse whether the provisions of bank secrecy are still relevant to protect the data and information of debtor customers; and how the bank secrecy rules in Indonesia compare with Malaysia and the UK in protecting debtor customers. This type of research is legal research that uses a statutory approach, conceptual approach and comparative legal approach. The results of this study indicate that protecting debtor customer data and information through bank secrecy rules is relevant. Protection of data and information of all customers is necessary because it is a human right that has been guaranteed in the constitution, besides that personal data has a certain financial value and has become a tradable asset commodity. Debtor customers have an equally important position as depositors, the bank's intermediary function will not run without the activity of channeling funds to debtor customers. Therefore, in special circumstances, debtor customers with current credit collectibility can be considered to be protected in bank secrecy. Malaysia and the UK provide more adequate protection of debtor customer data and information compared to Indonesia, which limits the scope of bank secrets to depositors and their deposits.